2022
DOI: 10.3389/fnins.2022.828029
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Model for Frontotemporal Dementia Diagnosis Using T1-Weighted MRI

Abstract: Radiomics has been proposed as a useful approach to extrapolate novel morphological and textural information from brain Magnetic resonance images (MRI). Radiomics analysis has shown unique potential in the diagnostic work-up and in the follow-up of patients suffering from neurodegenerative diseases. However, the potentiality of this technique in distinguishing frontotemporal dementia (FTD) subtypes has so far not been investigated. In this study, we explored the usefulness of radiomic features in differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…In the current study, we found that patients with PPD_bvFTD+ Di Benedetto et al, 2022;Meyer et al, 2017;Möller et al, 2016;Tafuri et al, 2022). They have generally reported optimal performance of this approach in distinguishing patients with bvFTD from controls.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the current study, we found that patients with PPD_bvFTD+ Di Benedetto et al, 2022;Meyer et al, 2017;Möller et al, 2016;Tafuri et al, 2022). They have generally reported optimal performance of this approach in distinguishing patients with bvFTD from controls.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, our findings provided new evidence about morphometric changes associated with bvFTD in patients with a long history of PPD. Different studies have applied machine learning‐based classification of patients with bvFTD based on patterns arising from MRI (Di Benedetto et al., 2022 ; Meyer et al., 2017 ; Möller et al., 2016 ; Tafuri et al., 2022 ). They have generally reported optimal performance of this approach in distinguishing patients with bvFTD from controls.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the differentiation between the two PPA variants, our combined model achieved a diagnostic accuracy of 93.7% on the test set. This result overcomes the state-of-the-art performances achieved using only classical morphometry measurements ( Agosta et al, 2015 ; Bisenius et al, 2017 ; Kim et al, 2019 ; Lampe et al, 2022 ) and radiomics on gray matter ROIs ( Tafuri et al, 2022a ), in conjunction with machine learning systems like Support Vector Machine, Random Forest, or Linear Discriminant Analysis. It’s worth noting that, contrary to the comparison between pathological and healthy subjects, clinical/cognitive variables were unable to correctly identify the PPA phenotype achieving a suboptimal accuracy of classification of the 77.1%.…”
Section: Discussionmentioning
confidence: 82%
“…Consequently, numerous studies have employed the radiomics approach to uncover imaging biomarkers in cancers ( Vial et al, 2018 ) and, more recently, to evaluate diagnosis and prognosis in other diseases, including neurodegenerative conditions ( Salvatore et al, 2019 ; Feng and Ding, 2020 ; Tafuri et al, 2022a ). In particular, classification models have been developed by extracting high-dimensional sets of radiomics measures in specific brain regions and then combining feature selectors and machine learning algorithms to distinguish between diagnostic categories ( Feng et al, 2018 ; Ranjbar et al, 2019 ; Tafuri et al, 2022a , b ; Rajagopalan et al, 2023 ). Despite the optimal performance obtained by these classification frameworks, however, the estimation of each feature contribution to the model’s classification is often unclear limiting the interpretability of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning, tailored for intricate multivariate data, holds promise as an adjunct in the diagnostic process by offering decision support [25]. Previous studies have use machine learning algorithms to classify between the subtypes of dementia [25][26][27] and subtypes of FTD [28,29] in structural MRI. The accuracy of machine learning model between subtypes of FTD was ranged from 0.7-0.94.…”
Section: Introductionmentioning
confidence: 99%